2010
DOI: 10.1111/j.1365-294x.2010.04713.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcodes show cryptic diversity and a potential physiological basis for host specificity among Diplostomoidea (Platyhelminthes: Digenea) parasitizing freshwater fishes in the St. Lawrence River, Canada

Abstract: Diplostomoid metacercariae parasitize freshwater fishes worldwide and cannot be identified to species based on morphology. In this study, sequences of the barcode region of cytochrome c oxidase subunit 1 (CO1) were used to discriminate species in 1088 diplostomoids, most of which were metacercariae from fish collected in the St. Lawrence River, Canada. Forty-seven diplostomoid species were detected, representing a large increase in known diversity. Most species suggested by CO1 sequences were supported by sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
142
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(151 citation statements)
references
References 69 publications
(88 reference statements)
6
142
2
1
Order By: Relevance
“…The larger ML analysis indicated that D. ardeae may belong to a genus other than Diplostomum, Tylodelphys or Austrodiplostomum, and that Tylodelphys may be paraphyletic, as Austrodiplostomum is nested within it. A CO1 sequence (HM064650) from a specimen formerly identified only to family (Locke et al, 2010b) fell within the Diplostomum clade, and is thus considered a member of the genus (Diplostomum sp. 11).…”
Section: Species Discrimination With Co1mentioning
confidence: 99%
“…The larger ML analysis indicated that D. ardeae may belong to a genus other than Diplostomum, Tylodelphys or Austrodiplostomum, and that Tylodelphys may be paraphyletic, as Austrodiplostomum is nested within it. A CO1 sequence (HM064650) from a specimen formerly identified only to family (Locke et al, 2010b) fell within the Diplostomum clade, and is thus considered a member of the genus (Diplostomum sp. 11).…”
Section: Species Discrimination With Co1mentioning
confidence: 99%
“…When correcting for study effort and accounting for other confounding variables, cryptic species do not appear to be more frequent among parasitic than free-living taxa (Poulin & Pérez-Ponce de León, 2017). Yet cryptic parasite species are reported with increasing frequency; this is a consequence of genetic methods having become standard practice for parasite identification, and often being used deliberately to prospect for cryptic diversity (Blouin, 2002;Locke et al, 2010;Rosas-Valdez et al, 2011;Razo-Mendivil et al, 2015). For parasitologists, there are serious implications: the occurrence of cryptic parasite species can greatly complicate parasite taxonomy, bias estimates of host specificity and undermine our efforts to control parasitic diseases (Poulin & Keeney, 2008; Pérez-Ponce de León & Nadler, 2010;Nadler & Pérez-Ponce de León, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…of 47 studies, 11 expressing variations in ITS-1 region, 20 in ITS-2 region and 16 in both ITS-1 and ITS-2 region. Apart from ITS region, mitochondrial genes like COI, NDI (Caffara et al, 2014;Heneberg et al, 2014;Locke et al, 2011) etc. are also included to corroborate the fi ndings.…”
Section: Resultsmentioning
confidence: 99%
“…Locke et al (2010a) studied the barcode region of COI and ITS sequences to differentiate species of diplostomoids from fi shes in St. Lawrence River, Canada. 47 species of diplostomoids were noticed and COI sequences analysis was supported by ITS region data.…”
Section: Diplostomidae (Poirier 1886)mentioning
confidence: 99%
See 1 more Smart Citation